Inovasi Instrumen Penilaian Non Tes Maharah Kalam dengan Pembuatan Video Hiwar Kreatif di MAN 4 Banyuwangi - Sabrina, Banat; R Umi Baroroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this scientific study is to provide a non-test assessment tool by creating a creative dialogue video on the topic of shopping. This research was conducted using a qualitative approach with data collection. The primary data comes from eleventhgrade students at the Islamic State Senior High School 4 Banyuwangi, while the secondary data is sourced from relevant documents related to the research. The analyses show the results of using the assessment tool that evaluates speaking skills, where students are classified into several categories including fluency, pronounciation, grammar and activity. The results indicate that students in the "very competent" category make up 36%, while the "competent" category constitutes 54%, and the "somewhat competent" category accounts for 10%. Therefore, there is a need for a genuine assessment of speaking skills in performance evaluation, which can assess linguistic elements without neglecting the contextual aspect by evaluating dialogues, assignments, presentations, and interviews that align with the topic of the text. The assessment model has been developed to encompass all aspects of evaluation, which consist of knowledge, language skills, and attitudes.